From Simple Palladium(II) Monomers to 2D Heterometallic Sodium–Palladium(II) Coordination Networks with 2-Halonicotinates - Kodrin, Ivan (2024)
The 2D heterometallic sodium-palladium(II) coordination polymers with 2-halonicotinates (2-chloropyridine-3-carboxylate (2-chloronicotinate), 2-Clnic and 2-bromopyridine-3-carboxylate (2-bromonicotinate), 2-Brnic), {Na2(H2O)2(μ-H2O)4PdCl2(μ-2-Clnic-N:O´)2}n (1) and {Na2(H2O)2(μ-H2O)4PdBr2(μ-2-Brnic-N:O´)2·2H2O}n (2) were prepared in the aqueous solutions under presence of NaHCO3, whilst palladium(II) monomers with the neutral 2-chloronicotinic and 2-bromonicotinic acid ligands, PdCl2(2-ClnicH-N)2·2DMF (3) and PdCl2(2-BrnicH-N)2·2DMF (4), were prepared in the DMF/water mixtures (DMF = N,N’-dimethylformamide). The zigzag chains of water-bridged sodium ions are in turn bridged by [PdCl2(2-Clnic)2]2− moieties in 1 or by [PdBr2(2-Brnic)2]2− moieties in 2, leading to the formation of the infinite 2D coordination networks of 1 or 2. The DFT calculations showed the 2D coordination networks 1 and 2 are more stabilized by the formation of Na–Ocarboxylate bonds, comparing to the stabilization of palladium(II) monomers 3 and 4 by hydrogen-bonding with DMF molecules. The halosubstituents type (Cl vs. Br) doesn’t have an influence on the formation of either trans or cis isomers. The trans isomers were found in all reported compounds; being more stable for about 10 to 15 kJ mol−1. The difference in DFT calculated energy stabilization for 1 and 2 is ascribed to the type of halosubstituents and to the presence/absence of lattice water molecules in 1 and 2.